Stem/progenitor cells in the developing human liver: morphological and immunohistochemical features - Daniela Fanni; Clara Gerosa; Federica Lai; Peter Van Eyken; Gavino Faa (Hygeia Press di Corridori Marinella, 2016)
Stem/progenitor cells in the adult liver are able to differentiate both into hepatocyte and cholangiocyte lineage. The identification and the role of human liver stem/progenitor cells has been a challenge topic in the recent scientific literature. The existence of stem/progenitor cells in the liver was first claimed in experimental animal models. CD34, c-kit, cytokeratin 7, cytokeratin 19, α-fetoprotein, OV6 and CD90 were the first markers shown. The major support for the existence of hepatic stem/progenitor cells has come from studies on liver carcinogenesis, human liver disease and cirrhosis. Where exactly the putative stem/progenitor cells reside in the normal liver is still controversial and their specific anatomical location is still unclear. Preliminary data from our lab indicate the portal tracts as the preferential site of the stem cell niches thanks to the expression of biliary-type cytokeratin 19, SOX9 and c-kit. Small undifferentiated cells were easily identified in H&E as well. Like in other organs, hepatic stem/progenitor cell niche was hypothesized and described as composed of numerous cell types that interact and cross-talk with hepatic stem/progenitor cells. Hepatic stem/progenitor cells represent a heterogeneous population with a spectrum of morphological and immunohistochemical features ranging from bile duct cells to hepatocytes, including the multipotent hepatic stem/progenitor cells, the hepatoblasts, the committed progenitors and the diploid adult cells. Inside this complex and articulate spectrum, cells without hepatobiliary markers and hematopoietic stem/progenitor cells can be identified. The hepatic stem/progenitor cells exhibit specific population functions and can be identified by specific population immunohistochemical markers, including CD133, CXCR4, SOX9, SOX17, cytokeratins, Hedgehog proteins, MDR1 and many others. In conclusion, this study represents the basis for further studies, aimed at better characterizing these stem/progenitor cells and at identifying possible subtypes of hepatic stem progenitor cells. Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano